Inhibitor development against FVIII in previously treated patients with haemophilia A - Siegmund, B.; Pollmann, H.; Richter, H.; Orlovic, M.; Gottstein, S.; Klamroth, R. (Hämostaseologie, 2010)
In a retrospective study 118 haemophilia A patients from two treatment centres (Berlin and Muenster) were evaluated with respect to safety, i. e. inhibitor development, and efficacy of bleeding control of recombinant FVIII products. During approx. 57 thousand injections with more than 87 million I.U. rFVIII no de novo inhibitor was observed in patients previously treated with pFVIII after switch to a recombinant product. A total of 75 thousand injections with more than 111 million I.U. FVIII had been applied during the investigation period of 14 years. Before as well as after switch of the product type bleeding episodes could be controlled with one to two injections per bleed.According to our results equal safety and efficacy of plasma derived and recombinant FVIII products can be assumed.
Keywords: Haemophilia A; factor VIII; inhibitor; PTP